Performance Evaluation of Computer Campus Network Segments - Antonyuk, Ya.M. (Управляющие системы и машины, 2018)
The task of evaluating the performance of computer networks and their segments is considered - one of the main issues of the formation and functioning of modern campuses, educational spaces and corporate cloud solutions. To measure the characteristics of network performance, certain measurements were made on a sequence of packets arriving at some interface of a network device. Two types of existing measurements in the network are compared: active measurements and passive measurements. Conclusions are drawn about the possibility of measuring between any two nodes, or points, of the network based on preliminary data on the throughput capacity of individual network elements. The data transfer rate can be measured between any two nodes, or points, of a network, for example, between a client computer and a server, between the input and output ports of a router, and to analyze and configure the network to know the data on the throughput of individual network elements. Цель — разработка процедуры оценивания для активных измерений — на основании генерации в узлеисточнике специальных «измерительных» пакетов, для пассивных — на основании способов перехвата характеристик реального трафика. Методы. При разработке этой процедуры для построения оценочных алгоритмов использован набор процедур, рекомендованных RFC соответствующей тематики в сочетании со стандартными характеристиками структурного анализа сетевых инфраструктур. Результаты. Разработана методика анализа сетевых потоков в кампусных сегментах. Сделаны выводы о возможности измерений между любыми двумя узлами, или точками сети на основании предварительных данных о пропускной способности отдельных элементов сети. Мета. Метою даної статті є розробка процедури оцінювання. Для активних вимірювань — на підставі генерації в джерельному вузлі спеціальних «вимірювальних» пакетів, для пасивних — на підставі способів перехоплення характеристик реального трафіку. Методи. При розробці цієї процедури для побудови оціночних алгоритмів використано набір процедур, рекомендованих RFC відповідної тематики у поєднанні зі стандартними характеристиками структурного аналізу мережевих інфраструктур. Результати. Розроблено методику аналізу мережевих потоків у кампусних сегментах. Зроблено висновки про можливість вимірювань між будь-якими двома вузлами, або точками мережі на підставі попередніх даних про пропускну здатність окремих елементів мережі.